2018
DOI: 10.1111/jfbc.12502
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profiles, antioxidant, antimicrobial, and DNA damage inhibitory activities of chestnut honeys from Black Sea Region of Turkey

Abstract: Honey is the product of beekeeping that has great market potential thanks to valuable nutritional and medicinal qualities. Black Sea Region coast of Turkey is suitable for production of chestnut production so chestnut-based honeys are highly produced in this region. To prove the beneficial therapeutic properties, 49 chestnut (Castania sativa Mill.) honey samples from the cities of Black Sea Region were investigated in terms of colors, total phenolic and flavonoid contents, antioxidant activities, antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…In this method, the ferric ion (Fe 3+ ) was reduced to ferrous ion (Fe 2+ ) by antioxidant compounds, and the blue‐colored ferrous complex was produced at the end of the reaction (Habib, Al Meqbali, Kamal, Souka, & Ibrahim, ). The antioxidant capacity of CBPE obtained by the FRAP method was threefold larger than the antioxidant capacity values of 49 chestnut honey samples that were extracted with water and methanol (Ayvaz et al, ). Due to the different environmental conditions, locality of the sample, and extraction methods, the antioxidant properties can be changed from one sample to another.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this method, the ferric ion (Fe 3+ ) was reduced to ferrous ion (Fe 2+ ) by antioxidant compounds, and the blue‐colored ferrous complex was produced at the end of the reaction (Habib, Al Meqbali, Kamal, Souka, & Ibrahim, ). The antioxidant capacity of CBPE obtained by the FRAP method was threefold larger than the antioxidant capacity values of 49 chestnut honey samples that were extracted with water and methanol (Ayvaz et al, ). Due to the different environmental conditions, locality of the sample, and extraction methods, the antioxidant properties can be changed from one sample to another.…”
Section: Resultsmentioning
confidence: 99%
“…The main ROS compounds have been responsible for the formation of oxidative damage by attacking macromolecules, such as proteins and DNA. It is known that DNA oxidation is a cause of cancer, Alzheimer's disease, aging, and other genetic diseases (Ayvaz, Ömür, Ertürk, & Kabakçi, ). The investigation of the detection and prevention of DNA damage threatening human health has recently gained importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another form is formed III, which is a linear form and this form arises between form I and forms II. Plasmid analysis investigates the transformation of supercoiled plasmid DNA of radicals into linear or circular forms [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies strongly showed antioxidant protection effects against various diseases or illness relevant to oxidative stress, such as aging, cardiovascular diseases, cancer, stoke, diabetes, Alzheimer's disease, hypertension, and inflammation [1][2][3][4][5]. Various antioxidants from natural products are excellent candidates, e.g., phenolic acids, tannins, lignans, and flavonoids) [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%